Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
#)Giải :
\(x^2-y^2+3x-3y=\left(x-y\right)\left(x+y\right)+3\left(x-y\right)=\left(x-y\right)\left(x+y+3\right)\)
\(x^2-y^2+3x-3y\)
\(=\left(x-y\right)\left(x+y\right)+3\left(x-y\right)\)
\(=\left(x-y\right)\left(x+x+3\right)\)
~ Rất vui vì giúp đc bn ~
\(x^4y-3x^3y^2+3x^2y^3+xy^4=xy\left(x^3-3x^2y+3xy^2+y^3\right)\)
a) 3x^2 -6x + 3 - 3y^2
=3.(x2-2x+1-y2)
=3.[(x-1)2-y2]
=3.(x-1+y)(x-1-y)
\(x^3+y^3-3x-3y=\left(x+y\right)\left(x^2-xy+y^2\right)-3\left(x+y\right)\)
\(=\left(x+y\right)\left(x^2-xy+y^2-3\right)\)
\(x^3+y^3-3x-3y\)
<=> \( \left(x+y\right)\left(x^2-xy+y^2\right)-3\left(x+y\right)\)
<=>\(\left(x+y\right)\left(x^2+y^2-xy-3\right)\)
\(3x+3y-x^2-xy\)
\(=\left(3x+3y\right)-\left(x^2+xy\right)\)
\(=3\left(x+y\right)-x\left(x+y\right)\)
\(=\left(3-x\right)\left(x+y\right)\)
^2 + 4xy - 16 + 4y^2
= x^2 + 4xy + 4y^2 - 4^2
= (x + 2y)^2 - 4^2
= (x + 2y - 4)(x + 2y + 4)
2x^2-5xy-3y^2
= 2^x + xy - 6xy - 3y^2
= x(2x + y) - 3y(2x + y)
= (2x + y)(x - 3y)
\(=3\left(x^3-y^2\right)\)
Sửa: \(3x^2-3y^2=3\left(x^2-y^2\right)=3\left(x-y\right)\left(x+y\right)\)